Improving the thermostability and substrate affinity of IsPETase through the S209H mutation, and exploring the structural role of the N-terminal: a computational study - Nezhad, Nima Ghahremani; Buhari, Sunusi Bataiya; Eskandari, Azadeh; Albayati, Samah Hashim; Omotayo, Oluwaloni Folusho; Leow, Thean Chor (Springer Science and Business Media Deutschland GmbH, 2025)
The current in silico investigation aimed to increase the thermostability of IsPETase for more efficient PET degradation. N-Truncated and S209H mutants were designed to improve the thermostability of IsPETase. The deletion of the first seven N-terminal residues in PETase (N-truncated mutant) disrupts structural integrity, as Arg5, a crucial residue, maintains stability by forming a hydrogen bond network with Pro2, Thr48, Lys230, and Arg238. This links the N-terminal to the C-terminal, while its absence increases RMSF values in this region. The S209H mutation, located in the catalytic loop of IsPETase, enhances thermostability by introducing a new hydrophobic interaction with residue W130. MD simulations at 353.15 K have demonstrated this improvement, showing reduced structural flexibility and compactness in the S209H mutant compared to the WT. Specifically, the overall RMSD, Cα RMSD, SASA, and Rg values decreased from 3.36249 ± 0.853 Å, 1.321843 ± 0.0953 Å, 10,057.73 ± 135.11 Å2, and 17.09687 ± 1.387 Å in the WT to 3.184878 ± 0.786 Å, 0.969998 ± 0.119 Å, 9894.527 ± 118.53 Å2, and 16.962 ± 1.265 Å in the S209H mutant, respectively. Molecular docking revealed binding energies of -4.9 kcal/mol for WT, -5.1 kcal/mol for the S209H mutant, and -4.8 kcal/mol for the N-truncated mutant. MM-PBSA analysis using YASARA showed that the S209H mutation increased binding energy from -17.3606 kJ/mol (WT) to -7.82077 kJ/mol, enhancing binding affinity, while the N-truncated mutant reduced binding energy to -23.5032 kJ/mol, lowering binding affinity. In conclusion, this study has demonstrated that the S209H mutation enhanced the thermostability and the PET affinity of IsPETase by introducing the hydrophobic interactions. The N-truncated mutant reduced both thermostability and PET affinity, highlighting the critical role of the N-terminal region in maintaining the stability and activity of IsPETase.